Risk factors for development of melanoma brain metastasis and disease progression: a single-center retrospective analysis. Issue 5 (October 2017) - Gardner, Laura J.; Ward, Morgan; Andtbacka, Robert H.I.; Boucher, Kenneth M.; Bowen, Glen M.; Bowles, Tawnya L.; Cohen, Adam L.; Grossmann, Kenneth; Hitchcock, Ying J.; Holmen, Sheri L.; Hyngstrom, John; Khong, Hung; et al.
Abstract : Melanoma metastasis to the brain is associated with a poor prognosis. We sought to determine patient demographics and primary tumor factors associated with the development of brain metastasis (BM) and survival. We also investigated whether the BM detection setting (routine screening vs. symptomatic presentation) affected clinical outcomes. A database of melanoma patients seen from 1999 to 2015 at our institution was reviewed to identify patients who developed BM. Patients with BM were matched by initial stage with patients who did not develop BM as a control group. Patient demographics, primary tumor characteristics, and clinical outcomes were analyzed. A total of 123 patients with BM were matched by initial presenting stage to 237 patients without BM. The characteristics of the primary melanoma tumor associated with BM development included location on the scalp ( P =0.030), nodular histologic type ( P =0.020), and Breslow depth more than 4 mm ( P =0.048), whereas location on the leg was associated with decreased BM risk ( P =0.006). In patients with BM, time to first recurrence for melanomas of the scalp was significantly shorter (10.8 vs. 24.8 months, P =0.007) than nonscalp head and neck tumors. Patient stage, tumor depth, nodular type, and ulceration were also associated with worse clinical outcomes. There were no differences in the clinical outcomes between patients whose BM were detected upon routine screening versus those detected upon symptomatic presentation. In summary, factors predictive of development of BM included primary scalp location, nodular type, and depth. In BM patients, scalp location, stage, tumor depth, nodular type, and ulceration, but not detection setting, were associated with worse clinical outcomes. Abstract : Supplemental Digital Content is available in the text.